What are the causes of the growing trend of excess savings of the corporate sector in developed countries?: an empirical analysis of three hypotheses - Brufman, Leandro; Martinez, Lisana Belén; Perez Artica, Rodrigo
This paper analyzes annual accounting data for a sample of 5,000 publicly traded manufacturing firms from Germany, France, Italy, Japan, and the United Kingdom. The analysis uses data from 1997 to 2011 and finds an increasing trend of excess savings (defined as the difference between gross saving and capital formation) and a gradual decline of gross capital formation. This trend is accompanied by a steady deleveraging process and a decrease in the share of operating assets in total assets. This process is more acute among the more credit constrained, the more volatile, and the less dynamic firms. Fil: Brufman, Leandro. World Bank. Treasury Department; Estados Unidos Fil: Martinez, Lisana Belén. Universitat Rovira I Virgili; España. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Perez Artica, Rodrigo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Investigaciones Económicas y Sociales del Sur. Universidad Nacional del Sur. Departamento de Economía. Instituto de Investigaciones Económicas y Sociales del Sur; Argentina